Gender ideology, religion and the politics of bodies: The contemporary dispute for the control of cultural senses (Research, Society and Development, 2021)
The underlying theme of this article deals with the contemporary dispute for cultural meanings, or what others call cultural war, on women's sexual and reproductive rights and LGBTQIA+ dissenting sexualities from the debate around the theme of gender and/or ideology named by conservative religious groups. The article starts from the analysis of papal documents and the Brazilian episcopate, from the UN international conferences on women and from recent tensions on the subject in Brazilian society. The results demonstrate that this growing confrontation over the choice of the issue involving rights over women's bodies and sexual dissidences takes place within the historical-structural context of the transition of epochs. The shift from industrial modernity to post-industrial times challenged elementary aspects of modernity such as: the definition of personhood; the notion of citizenship; the boundaries between public and private; the relationship between church and state and the nature of the national project. In this way, the article identifies the complexity of the theme from the analysis of the position of the Catholic hierarchy and contextualizes the historical and structural moment in which the dispute intensifies, especially in the Brazilian case.